English Technical study for the production of gelatin based on fish scales in the city of Portoviejo. - Cedeño Campuzano, Maria Gabriela (2025)
The present research is in effect in response to the economic development that implies changes in the cities and the needs that exist in the Canton, Crucita being the strategic place to demand investment in machinery, labor, raw materials, land and construction for a total of $117 434, mentioned this, the objective was to carry out a technical study for the production of gelatin based on fish scales in the city of Portoviejo. The research to be used was descriptive and non-experimental; a theoretical, empirical and mathematical methodology was used that allowed the development of the proposed study. The installed capacity for the development of the production of gelatin based on fish scales will be 500 pounds per week. Through the application of the survey technique instrument that was directed to 385 participants from the Portoviejo Canton, including the application of interviews with fishing artisans, the results were obtained, indicating that 91% of those surveyed show interest in one of the products. to consider, with a presentation of 400 gr containers at a price of $2,50, on the other hand, there is the possibility of expanding demand and production at a national level, for this reason, the study presents a complete and solid vision of the viability of the creation of the gelatin processing plant based on fish scales, thus providing great opportunities in the market, both labor, economic and at the industry level.